Peran BMT dalam memberdayakan Usaha Mikro melalui Pembiayaan Al-Qardhul Hasan: Studi Kasus pada BMT Darussalam Madani Kota Wisata Gunung Putri Bogor - Darmawan Hamzah; Suprihatin . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
This research aims to determine the role BMT in empowering micro entrepreneurs with qardh al-hasan financing. The method used naturalistic qqualitative mmethods with data collection techniques, namely: interview, documentation submitted to the manager and employee BMT Darussalam Madani and micro entrepreneurs. Based on the research results in the empowerment of business micro BMT Darussalam Madani through qardh al-hasan financing funds from the zakat, Infaq, shadaqoh and from the donation that is given to the micro entrepreneurs who run their business. Most of the micro-entrepreneurs who have received financial assistance qardh al-hasan has developed its business volume, due to the capital relief. However, there are still some constraints factors, internally is their limited financial resources qardh al-hasan, externally there are micro entrepreneurs who are not disciplined in financial aid refund qardh al-hasan.